A Narrative Review of Current Advances and Future Changes Regarding Bladder Cancer Treatment - Dominik Godlewski; Sara Czech; Jakub Szpara; Dorota Bartusik-Aebisher; David Aebisher (Uro)
Bladder cancer (BC) remains a clinical challenge due to its complex etiology and high incidence, especially in developed populations. This article presents a broad analysis of the latest advances in BC treatment, offering a new perspective on the growing role of innovative therapies that are effectively changing the standards of oncological care. Focusing on targeted therapy, immunotherapy, antibody–drug conjugates, and breakthrough gene therapies, the paper shows how modern approaches can counteract resistance mechanisms and improve treatment efficacy while limiting toxicity for patients. Progress in the field of immune therapies, including checkpoint inhibitors, offers hope for significant improvement in the outcomes of patients with advanced forms of cancer, and the concept of targeted therapy tailored to the molecular characteristics of the tumor indicates the potential of personalized oncology. Gene and photodynamic therapies, in turn, offer new possibilities for precise action on cancer cells, minimizing the side effects of traditional methods. The article presents innovative therapeutic strategies and results of the latest clinical trials, showing the prospects for the development of BC treatment and highlighting the key challenges facing oncology.